BODY IMAGE AND SELF-ESTEEM AS PSYCHOLOGICAL DETERMINANTS OF WOMEN’S REPRODUCTIVE HEALTH BEHAVIOR: A NARRATIVE REVIEW - Siska Putri Belangi; Yessy Syahradesi Br Tambunan; Dina Andriani; Fika Lestari (EZRA SCIENCE BULLETIN, 2026)
Women’s reproductive health behavior is influenced not only by biological and social factors but also by psychological determinants such as body image and self-esteem. This study aimed to synthesize scientific evidence on the role of body image and self-esteem as psychological determinants of women’s reproductive health behavior. A narrative review design was used, with a literature search conducted in PubMed, Scopus, ScienceDirect, and Google Scholar for articles published between 2014 and 2025. Studies were selected based on predefined criteria, including those involving women of reproductive age and examining the relationship between body image and/or self-esteem and reproductive or sexual health outcomes. The findings consistently indicated that positive body image and higher self-esteem were associated with better sexual function, greater sexual satisfaction, improved reproductive well-being, and healthier reproductive decision-making. Conversely, negative body image was linked to poorer psychological and sexual well-being. These results highlight the importance of integrating psychosocial interventions into reproductive health promotion to support women’s overall reproductive health outcomes.